Bioelectrical impedance analysis, hydrometry and hydrodensitometry for body composition assessment in adult Colombian women. (July 2019) - Caicedo-Eraso, J C; Gonzalez-Correa, C H; Gonzalez-Correa, C A; Gallagher, D
Abstract: Bioelectrical impedance analysis (BIA) is a noninvasive method for assessment of body composition with better accuracy, and less inter-observer error than anthropometry. Despite these advantages, reported BIA equations may not be suitable for populations other than where they were developed. The aim of this study was to develop equations for single-frequency (SF) BIA and bioelectrical impedance spectroscopy (BIS) using a three compartment (3C) model as the criterion method to predict total body water (TBW) and fat-free mass (FFM) in South-American adult women. A cross-sectional observational study was conducted using a convenience sample (n=40). SF-BIA and BIS prediction equations were developed using forward-stepwise multiple regression with TBW by D2 O and FFM by 3C model as dependent variables; and weight, resistance and impedance index (stature 2 /resistance) as independent variables. A cross-validation was conducted in a randomly split subsample (n=20). Four final equations were developed. There were no differences between SF-BIA and BIS equations for TBW (p=0.68) and FFM (p=0.66). The cross-validation showed a strong association and broadly meets the limits of agreement with the 3C reference method. The equations have an excellent goodness-of-fit to predict TBW and FFM. Validation of these equations in populations of different ages and ethnicities is warranted.